Caracterización Macroscópica De Morteros Romanos De Tipo Industrial En Villamanta (Madrid). Primeros Datos - García, Pablo Guerra; Martín, Isabel Marqués; Medel, Alejandro Bermúdez; Romero, Alberto Polo (European Scientific Journal, ESJ, 2017)
The objective of this article is to show the results obtained from the physical and macroscopic characterization of the mortars sampled by Isabel Marqués and Alejandro Bermúdez, archaeological directors of the intervention carried out in El Tejar settlement, in the municipality of Villamanta (Madrid, Spain). The results of this work have determined a relevant typological classification among the samples, highlighting the presence of siliceous aggregates, ceramics in some mortars, a very varied grading and a distribution of the components that have conditioned the conservation. Of the four samples taken -VMT1 to VMT4- one of them has an aqueous pigmentation, belonging to an inside plaster, while the others correspond to lime mortars with aggregates from hydraulic surfaces. The archaeological investigation of the deposit of Villamanta is complemented by an implementation check of lime mortars, being one of the most important Roman context of Madrid. This research add a sequence of new results around the Roman mortars and implements a methodology in the study of the historical mortars.